Estrogen receptor ligands: a patent review update. (October 2013) - Paterni, Ilaria; Bertini, Simone; Granchi, Carlotta; Macchia, Marco; Minutolo, Filippo
<x xml:space="preserve">Abstract</x> Introduction: The role of estrogens is mostly mediated by two nuclear receptors (ERα and ERβ) and a membrane-associated G-protein (GPR30 or GPER), and it is not limited to reproduction, but it extends to the skeletal, cardiovascular and central nervous systems. Various pathologies such as cancer, inflammatory, neurodegenerative and metabolic diseases are often associated with dysfunctions of the estrogenic system. Therapeutic interventions by agents that affect the estrogenic signaling pathway might be useful in the treatment of many dissimilar diseases. Areas covered: The massive chemodiversity of ER ligands, limited to patented small molecules, is herein reviewed. The reported compounds are classified on the basis of their chemical structures. Non-steroidal derivatives, which mostly consist of diphenolic compounds, are further segregated into chemical classes based on their central scaffold. Expert opinion: Estrogens have been used for almost a century and their earlier applications have concerned interventions in the female reproductive functions, as well as the treatment of some estrogen-dependent cancers and osteoporosis. Since the discovery of ERβ in 1996, the patent literature has started to pay a progressively increasing attention to this newer receptor subtype, which holds promise as a target for new indications, most of which still need to be clinically validated.